Discovery of a novel series of guanidinebenzoates as gut-restricted enteropeptidase and trypsin dual inhibitors for the treatment of metabolic syndrome. (15th May 2021) - Zhang, Xuqing; Zhu, Bin; Sun, Weimei; Wang, Mina; Albarazanji, Kamal; Ghosh, Brahma; Cummings, Maxwell; Lenhard, James; Leonard, James; Macielag, Mark; Lanter, James
Graphical abstract: A novel series of guanidinebenzoate enteropeptidase and trypsin dual inhibitors has been discovered and SAR studies were conducted. Optimization focused on improving properties for gut restriction, including increased aqueous solubility, lower cellular permeability, and reduced oral bioavailability. Lead compounds were identified with efficacy in a mouse fecal protein excretion study. Abstract: A novel series of guanidinebenzoate enteropeptidase and trypsin dual inhibitors has been discovered and SAR studies were conducted. Optimization was focused on improving properties for gut restriction, including increased aqueous solubility, lower cellular permeability, and reduced oral bioavailability. Lead compounds were identified with efficacy in a mouse fecal protein excretion study.